The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences